COMPLEX THERAPY OF ADENOIDITIS IN CHILDREN - M. M. Polunin; L. S. Titarova; T. A. Polunina (Union of pediatricians of Russia, 2012)
Infections of the upper respiratory tract occupy a leading position among child diseases. During the past few years the number of children suffering from adenoiditis tends to increase. This article covers in detail the special features of etiology, clinical presentation, diagnosis, differential diagnostics, and treatment of this disease. The role of lymphoid formations in the formation of the upper respiratory immune system is also described in detail. The authors stress the necessity to increase indications for using conservative methods of treatment and warn against undertaking unfounded surgical interventions. The conservative treatment of an adenoid should be complex and should include irrigational therapy of the oral cavity and nasopharynx, local and systemic antibacterial therapy. A special attention is devoted to the usage of mucolytic drugs. We offer an observation of using an expectorant plant-based   an antiinflammatory, antibacterial effect, which promotes the reduction of the phlegm viscosity its better discharge.